Clinical and paraclinical parameters association to complications after abdominal closure following vacuum-assisted closure therapy in secondary peritonitis: A retrospective cohort study - Ask Vang; Pooya Rajabaleyan; Sören Möller; Sardar Khalaf; Uffe Tange Holst; Pedja Cuk; Benjamin Schnack Brandt Rasmussen; Thomas Strøm; Mark Bremholm Ellebaek (Langenbeck's Archives of Surgery, 2026)
Abstract Purpose To evaluate clinical and paraclinical parameters at the time of abdominal closure following vacuum-assisted closure (VAC) therapy in patients with secondary peritonitis, and to identify associations to postoperative complications. Methods This retrospective multicenter cohort study included patients with secondary peritonitis from the small intestine, colon, or rectum who underwent emergency laparotomy and VAC therapy at six hospitals in southern Denmark between 2010 and 2019. Clinical status and laboratory values obtained before abdominal closure were recorded. Complications within 30 days were graded using the Clavien-Dindo Classification. Results The cohort comprised 163 patients divided into two groups: 49 patients with postoperative complications and 114 without. Absence of bowel function (41% vs. 25%, p = 0.026), elevated creatinine levels (median [IQR]: 73 µmol/L [54–119] vs. 61 µmol/L [47–79], p = 0.036) and increased PCT levels (median [IQR]:13.8 µg/L [6.3–20.8] vs. 3.8 µg/L [1.3–8.6], p = 0.013) prior to closure, were associated with surgical complications. Lower eGFR levels (median [IQR]: 76 ml/min/1.73 m² [57–90] vs. 103 ml/min/1.73 m², [71–116], p = 0.025) and higher CRP levels (median [IQR]: 229 mg/L [148–354] vs. 153 mg/L [86–230], p = 0.002) before closure, were associated with medical complications. Conclusion In VAC therapy for secondary peritonitis, the risk of complications following abdominal fascial closure was increased if prior to closure bowel function had not returned, renal function was impaired and systemic inflammation was pronounced.